SISTEM INTERLOCK PADA MESIN HOT SAW DI AREA SECTION MILL PT. KRAKATAU BAJA KONSTRUKSI - Andi Purwanto; Mohammad Fatkhurokhman (Teknika, 2026)
This study discusses the implementation of an interlock system on the Hot Saw machine at the Section Mill area of PT. Krakatau Baja Konstruksi as an effort to improve operational safety and efficiency during the hot steel cutting process. The Hot Saw operates under extreme conditions of high temperature and speed, thus requiring a reliable safety mechanism to prevent workplace accidents and equipment damage. The research employed a descriptive-analytical method, which included literature review, field observation, system description, and descriptive analysis. Data were obtained through direct observation of the Hot Saw operation and its interlock components, such as limit sensors, safety switches, a control system based on Siemens S7-1500 PLC, and standard operational procedures. The findings indicate that the implemented interlock system ensures the machine operates only when all safety conditions are fulfilled and automatically stops the process if anomalies or system failures are detected. The integration of the alarm failure main drive saw feature also enhances operator responsiveness in identifying and addressing system malfunctions. Overall, the interlock system significantly contributes to improving work safety, machine reliability, and production continuity in the steel industry environment.